“The Knowledge of Literature”: or The Special Effects of Literary Discourse - Locatelli, Angela (Armenian Folia Anglistika, 2011)
Literature possesses huge knowledge value and social significance which, however, have not received due attention so far. The reason for such neglect is the fact that literature does not easily and immediately display its complex cognitive wonders. Rather, it is possible to perceive them after a long journey of evaluation and re-evaluation. Literature does not only provide an imaginary aesthetic picture, but also various expressions of consciousness and social identity.